Price Level Targeting with Imperfect Rationality: A Heuristic Approach - Vojtech Molnar (Charles University in Prague, Institute of Economic Studies (IES), 2021)
The paper compares price level targeting and inflation targeting regimes in a New Keynesian model with bounded rationality. Economic agents form their expectations using heuristics - they choose between a few simple rules based on their past forecasting performance. Two main specifications of the price level targeting model are examined - the agents form expectations either about price level or about inflation, which is ex ante not equivalent because of sequential nature of the model. In addition, several formulations of the forecasting rules are considered. Both regimes are assessed by loss function comparison. According to the results, price level targeting is preferred in the case with expectations created about price level under the baseline calibration; but it is sensitive to some model parameters. Furthermore, when expectations are created about inflation, price level targeting over time loses credibility and leads to divergence of the economy. On the other hand, inflation targeting model functions stably. Therefore, while potential benefits of price level targeting have been confirmed under certain assumptions, the results suggest that inflation targeting constitutes more robust choice for monetary policy.
Keywords: E31; E37; E52; E58; E70; 330; Price level targeting; Inflation targeting; Monetary policy; Bounded rationality; Heuristics